Data visualisation in continuous integration and delivery: Information needs, challenges, and recommendations - Azeem Ahmad; Ola Leifler; Kristian Sandahl (IET Software, 2022)
Abstract Several operations, ranging from regular code updates to compiling, building, testing, and distribution to customers, are consolidated in continuous integration and delivery. Professionals seek additional information to complete the mission at hand during these tasks. Developers who devote a large amount of time and effort to finding such information may become distracted from their work. We will better understand the processes, procedures, and resources used to deliver a quality product on time by defining the types of information that software professionals seek. A deeper understanding of software practitioners' information needs has many advantages, including remaining competitive, growing knowledge of issues that can stymie a timely update, and creating a visualisation tool to assist practitioners in addressing their information needs. This is an extension of a previous work done by the authors. The authors conducted a multiple‐case holistic study with six different companies (38 unique participants) to identify information needs in continuous integration and delivery. This study attempts to capture the importance, frequency, required effort (e.g. sequence of actions required to collect information), current approach to handling, and associated stakeholders with respect to identified needs. 27 information needs associated with different stakeholders (i.e. developers, testers, project managers, release team, and compliance authority) were identified. The identified needs were categorised as testing, code & commit, confidence, bug, and artefacts. Apart from identifying information needs, practitioners face several challenges in developing visualisation tools. Thus, 8 challenges that were faced by the practitioners to develop/maintain visualisation tools for the software team were identified. The recommendations from practitioners who are experts in developing, maintaining, and providing visualisation services to the software team were listed.